Resource-Richness and Economic Growth in Contemporary U.S. - Richard Jaimes; Reyer Gerlagh (Center for Economic Studies and ifo Institute (CESifo), 2017)
Between 1997 and 2014, US corn, soybean and cotton production almost fully converted to genetically modified crops. Starting around 2007, improved tight oil and shale gas technologies turned the declining US fossil fuel production into a booming industry. We study the effects of these two resource technology revolutions on US state income. We find that the shale revolution increased income in states abundant in oil and gas resources. States dependent on agricultural production also saw an increase in income, which we, however, attribute not to the GM innovation, but to a demand increase brought by the Energy Policy Act of 2005. We also document the resource boom indirect effects on other growth-enhancing activities, particularly, on private and public education expenditures, and distortionary taxation.
Keywords: C21; C23; I25; H72; O13; Q33; 330; natural resources; economic growth; resource curse; resource blessing